Interactive effect of grain size and crystal structure on deformation behavior in progressive micro-scaled deformation of metallic materials. (January 2020) - Tang, X.F.; Shi, S.Q.; Fu, M.W.
Abstract: Progressive micro-scaled deformation is an efficient approach to fabricating microparts directly using metal sheets. However, how the size effect and material crystal structure affect the deformation of metallic materials in the deformation process has not yet been well understood. In this research, a progressive micro-scaled deformation of metallic materials with different crystal structures and grain sizes was conducted to realize a multi-stage deformation and produce microparts directly using metal sheets via piercing, two step extrusion, and blanking. A unified mechanism-based constitutive model was proposed to describe the grain size dependent flow stress by incorporating dislocation glide and deformation twinning. The constitutive equations were implemented into the finite element model to simulate the progressive micro-scaled deformation. The deformation behavior of the microparts made of FCC pure copper, BCC pure iron, and HCP pure titanium with different size scales were thus extensively studied based on the material flow, strain pattern, microstructure evolution, and forming defect formation. The results show that the length of cylindrical micropin and the extrudates of the microformed parts by using FCC pure copper and BCC iron are decreased with the coarsening of grains. Deformation twins were prevalently formed in the produced micropin and micropart using HCP pure titanium with coarse grains and the dependency of their length on the initial grain size became unnoticeable. The irregular geometric defects include burr, incline, rollover, and bulge. The burr and rollover of extruded micropart are generally deteriorated with the increasing grain size for the three used materials, whereas the dimension of incline is not significantly affected by the initial grain size. All of these provide more insights into the progressive micro-scaled deformation of metallic materials for making bulk microparts. Graphical abstract: Image 1 Highlights: A mechanism-based constitutive model considering size dependent dislocation glide and deformation twinning was developed. Synergetic effect of grain size and crystal structure exists in progressive micro-scaled deformation for making microparts. Grain size effect on the dimension of microformed part is apparent for FCC copper and BCC iron but not for HCP titanium. Burr and rollover in the microparts made of BCC iron are more severe than that of FCC copper and HCP titanium.